Writing and Publishing Science Research Papers in English A Global Perspective - Englander, Karen; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book provides a comprehensive review of the current knowledge on writing and publishing scientific research papers and the social contexts. It deals with both English and non-Anglophone science writers, and presents a global perspective and an international focus. The book collects and synthesizes research from a range of disciplines, including applied linguistics, the sociology of science, sociolinguistics, bibliometrics, composition studies, and science education. This multidisciplinary approach helps the reader gain a solid understanding of the subject. Divided into three parts, the book considers the context of scientific papers, the text itself, and the people involved. It explains how the typical sections of scientific papers are structured. Standard English scientific writing style is also compared with science papers written in other languages. The book discusses the strengths and challenges faced by people with different degrees of science writing expertise and the role of journal editors and reviewers.
1 Introduction -- Part I The Context. 2 The Rise of English as the Language of Science -- 3 Measuring the Impact of Articles, Journals and Nations -- 4 English Competence, Funds for Research, and Publishing Success -- 5 Collaborations, Teams and Networks -- Part II The Text -- 6 The Scientific Research Article and the Creation of Science -- 7 Varieties of Science Texts -- 8 Structure of the Research Article in the Creation of Knowledge -- 9 Writing the Five Principal Sections: Abstract, Introduction, Methods, Results and Discussion -- 10 Variations in Different Languages and Cultures -- Part III The People -- 11 Graduate Students Becoming Scientists -- 12 Novice Scientists and Expert Scientists -- 13 English-Speaking Scientists and Multilingual Scientists -- 14 Gatekeepers, Guardians and Allies -- 15 Afterword: Negotiating Research Article Writing and Publication.
Keywords: Education; Language and languages; Literacy; Education; Language Education; Literacy